Defining and Measuring Housing Location in Appraisal and Hedonic Price Models: A Systematic Review - Bagaskara Bagaskara; Wakhid Slamet Ciptono (Universitas Ahmad Dahlan, Yogyakarta, 2026)
Location is a complex, multidimensional aspect often highly preferential and dependent on personal preference. In general discussions, this may not pose a significant problem. However, in quantitative analyses such as housing appraisals (sales comparison approach) or applied research using the hedonic price model, the nature and characteristics of location can become a major issue. Even though location is often included in housing studies, there is no clear and straightforward way to measure it as a single variable. This challenge is exacerbated in Indonesia due to the lack of a valid and reliable property database. Therefore, this study conducts a systematic review that contributes to the understanding of how location can be measured objectively. The present study aims to propose an alternative method for defining and measuring the strategic location of housing in appraisal practice, particularly through the sales comparison approach. Based on the review, location is measured using two aspects: spatial aspects and circumstantial aspects. Generally, spatial aspects are much more dominant than circumstantial aspects. The identified location dimensions include distance to the Central Business District (CBD), transportation facilities, commercial/shopping centers, employment centers, health facilities, educational facilities, recreational areas, as well as the conditions and accessibility to these amenities. The results of this study provide practical implications for improving the accuracy of property appraisal practices and offer a useful reference for future research, particularly in data-limited contexts such as Indonesia.